Assessment of geographical based load forecast approach in distribution planning - Soni, Monde (Department of Electrical Engineering, 2019)
Prior to the year 2007, Eskom Distribution followed a method of load forecasting (now referred to as legacy method in this report) that was based on collecting customer applications, historical load trending, and relied on the planner’s knowledge of the area to a large extent. It was based in a conventional Microsoft Excel spreadsheet. On seeking to improve its load forecasting approach, the utility adopted a technique that was based on spatial forecasting. This new technique was called a geographical based load forecasting (GLF) technique which was performed by using a custom based tool, called PowerGLF. The aim of this research was to assess any improvements (or lack thereof) that were brought about by adopting the GLF method as compared to the legacy method that was used previously. The hypothesis to be tested was declared as: “The use of the GLF method that was introduced to Eskom Distribution Planning brings about the improvement on the planning process of infrastructure that is adequate, reliable and economic, when compared to the legacy method that was used before it.” To carry out this assessment, a case study method was followed. Real network studies that were compiled in 2006 and 2007 were used. These network studies were based on GLF method and the legacy method. The load forecasts from the case studies were evaluated on forecast accuracy, how they influenced the planning of adequate, reliable and economic (ARE) network infrastructure and their impact on the procurement and construction of the network infrastructure (which represent the actual utility expenditure on infrastructure). The statistical comparative analysis was done. The research results revealed that the legacy method was more accurate than the GLF method in both the case studies that were evaluated. However, regarding the ability of a load forecast method to support the planning process, the GLF method showed to be supporting the planning of adequate, reliable and economic infrastructure better than the legacy method. It was found that the forecast error for the GLF and legacy method do not affect the utility infrastructure procurement and construction. Based on the test results, the study reached a conclusion that the use of the GLF method that was introduced to Eskom Distribution Planning brings about the improvement in the planning process of infrastructure that is adequate, economic and reliable when compared to the legacy method that was used before it. The author wishes to express that the results of this study must not be taken as a generic conclusive finding regarding the evaluated load forecasting methods; they are applicable to the tested case studies. To get to a general conclusive result, more case studies would need to be carried out where clear and consistent evidence on performance of these load forecasting methods will be seen. The findings of this study can be used as part of a larger sample if such a larger population of case studies was to be evaluated. The methodology followed in this research can be repeated and followed when similar assessments are done in future.